Biochemical Correlation of Sex Hormone Profile with Diabetes Mellitus Type 2 In Indian Men- A Case-Control Study - Kumar, Sandeep; Jain, Jaya; Jain, Ashutosh (Jurnal Ilmu Kesehatan dan Kesehatan, 2023)
Introduction: India, the country with the highest prevalence of diabetes, has between 62,4 and 77,2 million diabetics and pre-diabetics. The purpose of this study was to investigate the biological correlation between sex hormone profile and type 2 diabetes in Indian men. Methodology: In this case-control study, total of 181 diabetic cases and 181 healthy controls were enrolled as per WHO norms. Along with clinic-demographical data, fasting blood glucose, Postprandial blood glucose, HBA1c, insulin, lipid profile and Testosterone, LH, FSH were measured and compared. Results: A non-significant difference was observed [p=0.7831] between different ages among the study population's case and control groups. The FPG, HbA1c, total cholesterol, LDL, triglycerides were significantly elevated in cases as compared to controls, except HDL and SHBG, showing non-significant differences. The spearman correlation between Testosterone and different parameters, and all the correlations showed a significant negative correlation. However, Testosterone Vs. Testicular Volume (ml) [r=0.2981], Testosterone Vs. HDL cholesterol(mmol/l) [r=0.04884] and Testosterone Vs. Calculated Free Testosterone (mmol/L) [r=0.007494] respectively shows significant positive correlation. Conclusion: Type 2 Diabetes male patients had lower testosterone levels. As a biomarker for Type 2 Diabetes, it is possible to measure changes in serum testosterone levels.